2000
DOI: 10.1038/sj.leu.2401825
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone marrow angiogenesis in B cell chronic lymphocytic leukemia

Abstract: Recent studies have shown that angiogenesis may be involved in the pathogenesis of hematopoietic malignancies, apart from its well-characterized role in the growth and metastasis of solid tumors. In this study, we quantified the degree of angiogenesis in B cell chronic lymphocytic leukemia (B-CLL) by measuring the microvessel density and hotspot density in bone marrow trephine biopsy sections with B-CLL involvement (n ‫؍‬ 12) and compared it to normal bone marrow sections (n ‫؍‬ 11). The B-CLL samples had a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
130
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(139 citation statements)
references
References 21 publications
5
130
0
4
Order By: Relevance
“…Increased microvessel density has also been reported in the bone marrow of patients with CLL. 9 We suggested that increased angiogenesis might play an important role in the survival of tissue-phase CLL cells by providing metabolic support. 5 In addition to its role in angiogenesis, VEGF has been found to be an autocrine survival factor for some cell types including solid tumour and endothelial cells, [10][11][12] as well as CLL cells.…”
Section: Introductionmentioning
confidence: 97%
“…Increased microvessel density has also been reported in the bone marrow of patients with CLL. 9 We suggested that increased angiogenesis might play an important role in the survival of tissue-phase CLL cells by providing metabolic support. 5 In addition to its role in angiogenesis, VEGF has been found to be an autocrine survival factor for some cell types including solid tumour and endothelial cells, [10][11][12] as well as CLL cells.…”
Section: Introductionmentioning
confidence: 97%
“…1 By measuring microvessel and hotspot densities in bone marrow trephine biopsies, Kini et al 2 showed that both parameters are higher in patients with B-cell lymphocytic leukemia (B-CLL) than in normal individuals, indicating that angiogenesis may be involved in the pathogenesis of this leukemia. Similar results were obtained by Wolowiec et al 3 who also found that B-CLL bone marrow displays a higher proliferative activity than normal bone marrow, as assessed by the mean number of nucleolar organizer regions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Increased microvessel density in marrow Letters to the Editor and lymph node and increased levels of certain pro-angiogenetic factors in the blood and urine of CLL patients were observed. 2 Ang-2 has a pivotal role in the disruption of stability and quiescence of mature vasculature that coincides with the reinitiation of vascular remodelling and angiogenic sprouting in adult, as occurs in tumors. Abnormal serum levels of angiopoietin-2 (Ang-2) were found in several hematological malignancies.…”
mentioning
confidence: 99%